2021
DOI: 10.5465/amp.2019.0103
|View full text |Cite
|
Sign up to set email alerts
|

Platform-Dependent Entrepreneurs: Power Asymmetries, Risks, and Strategies in the Platform Economy

Abstract: Online digital platforms organize and mediate an ever-increasing share of economic and societal activities.Moreover, the opportunities that platform-mediated markets offer not only attract enormous numbers of entrepreneurs, but also support the growth of entire ecosystems of producers, sellers, and specialized service providers. The increased economic and business significance of digital platforms has attracted an outpouring of studies exploring their power dynamics and general impact. This research has largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
142
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(152 citation statements)
references
References 66 publications
2
142
0
8
Order By: Relevance
“…Second, our research speaks to the emerging stream of platform research that focuses on the seller/complementor side, which has shown that sellers' performance depends on not only platform conditions, but also seller‐specific attributes such as reputation and experience (Cutolo & Kenney, 2020; Huang, Ceccagnoli, Forman, & Wu, 2013; Lanzolla & Frankort, 2016; O'Mahony & Karp, 2020; Rietveld et al, 2020; Rietveld & Eggers, 2018; Zhang et al, 2020). By showing that the effectiveness of platform governance is affected by the interactions between platforms and sellers, our results present a feedback loop in which a design change is followed by heterogeneous seller responses, which may support or detract from the platform's design goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, our research speaks to the emerging stream of platform research that focuses on the seller/complementor side, which has shown that sellers' performance depends on not only platform conditions, but also seller‐specific attributes such as reputation and experience (Cutolo & Kenney, 2020; Huang, Ceccagnoli, Forman, & Wu, 2013; Lanzolla & Frankort, 2016; O'Mahony & Karp, 2020; Rietveld et al, 2020; Rietveld & Eggers, 2018; Zhang et al, 2020). By showing that the effectiveness of platform governance is affected by the interactions between platforms and sellers, our results present a feedback loop in which a design change is followed by heterogeneous seller responses, which may support or detract from the platform's design goals.…”
Section: Discussionmentioning
confidence: 99%
“…1 To manage these exchanges, platforms implement design rules to shape participants' behavior (Baldwin & Woodard, 2009). In particular, digital platforms undergo frequent design changes by altering the algorithms underlying the design rules (Cutolo & Kenney, 2020; Kapoor & Agarwal, 2017; Kretschmer & Claussen, 2016). For example, a platform can change how different types of sellers are ranked in buyers' search results or add a chat box for buyers to communicate with sellers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this increased interest in digital platforms, and their general economic role in society, very few studies have specifically focused on understanding the service provider‐specific outcomes of digital platforms (e.g., Burtch et al, 2018; Cutolo and Kenney, 2020; Rietveld et al, 2020). This narrow and yet limited body of literature reports that several mechanisms, such as a platform’s communication practices (Boons et al, 2015), rules and actions (Kapoor and Agarwal, 2017), management of relationships with service providers (Rietveld et al, 2019) and dominance and governance (Rietveld et al, 2020), affect service provider participation and performance on digital platforms.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…While research confirms that the structure, nature, and boundaries of the service sector are rapidly changing in the platform economy (Karanović et al, 2020; Orlikowski and Scott, 2016: Ostrom et al, 2015), only a few studies have focused on understanding what this means from a service provider perspective [1] (e.g., Burtch et al, 2018; Cutolo and Kenney, 2020; Rietveld et al, 2020). For example, most research emphasizes the conditions that enable digital platforms to emerge and achieve market dominance rather than the service provider‐specific outcomes of digital platforms (McIntyre et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2.I was introduced to the concept of “Platform-Dependent Entrepreneur” (Cutolo and Kenney 2020) in the final stage of publishing this article, and see clear connection between the concept and that of my own conceptualization of platform-mediated labor.…”
mentioning
confidence: 98%